Design of Water PH Quality Monitoring System in PT SIER Industrial Area Based on Internet of Things at Waste Water Treatment Plant - Fajar Mei Dialaksito; Pressa Perdana Surya (Indonesian Vocational Research Journal, 2023)
PT SIER's Waste Water Treatment Plant manages industrial and domestic wastewater obtained from industrial activities in the PT SIER Industrial area. Waste Water Treatment Plant PT SIER has been established since 1980. Over time, growth and development industry is increasing so that it adds to the WWTP burden. With respect to the load the more heavy so need in take note a number of matter following among them Waste fluid contaminated products from the manufacturing process must be treated and controlled for its pH content, the volume of waste water to be treated, the quality of water resulting from the Waste Water Treatment Plant process Which expected, convenience in matter management water waste, energy sources, as well as costs low process operation. This study aims to cut the process of taking sample water waste until analysis laboratory For get results monitoring quality pH water. On study This writer make system monitoring quality pH water in area industry PT. SIER based Internet of Things on waste water treatment Plant. With utilizing ESP32 which is integrated by the Internet of Things (IOT) via the internet network from Wi-Fi routers. Results quality monitoring data water can seen in realtime passes appearance mark pH, mark TDS And mark Temperature Which accessed through smartphones nor PC so that mark water quality delivered to the Blynk app.